2002
DOI: 10.1345/aph.1a045
|View full text |Cite
|
Sign up to set email alerts
|

Agranulocytosis Associated with Initiation of Famotidine Therapy

Abstract: Although agranulocytosis is a rare adverse effect of famotidine, the pharmacist and physician should be aware of this potentially fatal event. If any patient treated with famotidine develops fever, the clinician should consider, among other things, performing a white blood cell count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Therefore, we presume that the possibility of drug-induced hepatitis or HCC-related increase in LFTs is much lower than that of HBV reactivation, although famotidine-induced hepatitis remains much less likely. Famotidine is also known to induce agranulocytosis 5) and can cause immunosuppression. However, the lowest white blood cell count and absolute neutrophil count in our patient were 2900/ml and 2240/ml, respectively, so the possibility of famotidine-induced agranulocytosis leading to HBV reactivation was thought to be quite low.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we presume that the possibility of drug-induced hepatitis or HCC-related increase in LFTs is much lower than that of HBV reactivation, although famotidine-induced hepatitis remains much less likely. Famotidine is also known to induce agranulocytosis 5) and can cause immunosuppression. However, the lowest white blood cell count and absolute neutrophil count in our patient were 2900/ml and 2240/ml, respectively, so the possibility of famotidine-induced agranulocytosis leading to HBV reactivation was thought to be quite low.…”
Section: Discussionmentioning
confidence: 99%
“…However, other drugs examined in this study, for example amitriptyline, can also induce agranulocytosis (Flanagan and Dunk 2008b), and the pK i and pK B values of this drug for H 2 R are within the therapeutic reference range (Table 1). Moreover, rare cases of agranulocytosis following therapy with the high-affinity H 2 R antagonist famotidine have been reported (Marcu et al 2002). Collectively, H 2 R antagonism as a cause of agranulocytosis/neutropenia during therapy with various drugs may be more relevant than was previously appreciated.…”
Section: Structure-activity Relationships For Antidepressants and Antmentioning
confidence: 98%
“…[2][3][4]9,10 Researchers discussing the nature of the reaction concluded that omeprazole produced a hypersensitivity reaction via a toxic mechanism, with no conclusively determined cause. 6,9,10 While there have been postmarketing reports of agranulocytosis in association with lansoprazole, this has not yet been reported in the literature. 11 To our knowledge, our study is the first to examine the relationship between coprescribed medications and the occurrence of hematological adverse effects in a sample of patients being treated with clozapine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 A second proposed mechanism for neutropenia is based on the formation of drug-dependent antibodies. 6 Olaison et al reviewed all beta-lactam orders with a duration of therapy greater than 10 days. 7 Of 215 orders, 70 (33%) were associated with an adverse reaction, 18 of which (8%) involved neutropenia.…”
Section: Literature Reviewmentioning
confidence: 99%